Pengaruh Model Discovery Learning terhadap Keterampilan Mengembangkan Hikayat ke Bentuk Cerpen Siswa - Febrina Riska Putri; Upit Yulianti DN; Dwiyan Rahma Putri (JUPE : Jurnal Pendidikan Mandala, 2022)
This research is motivated by the skills of developing folklore (saga) into the form of short stories for students who are still low. The problem found is that students have difficulty developing folklore (saga) into short story form because they do not understand the material to develop folklore (saga) into short story form. This has resulted in the ineffectiveness of learning to develop folklore (saga) into short stories in the classroom. This study aims to describe the effect of the discovery learning model to improve learning to develop folklore (saga) into short stories for class X students of SMA N 1 Gunung Talang. . The population of this research is the students of class X SMA N 1 X Gunung Talang in the academic year 2021/2022, totaling 252 people. Samples were taken in class X IPA 5 and X IPA 6, totaling 25 people. The research method used in this study is the research design used is a quasi-experimental (quasi-experimental). The instrument used in this study was student performance tests. The results of this study are first, the skills of developing folklore (saga) into short stories for class X SMA N 1 Gunung Talang without using the discovery learning model to get an average score of 57.6 including sufficient qualifications in the range of 56- 65%. Second, the skills of developing folklore (saga) into short stories for class X students of SMA N 1 Gunung Talang using the discovery learning model obtained an average score of 76.2 including good qualifications in the range of 76-85%. Third, there is a significant influence in the use of discovery learning models in developing folklore skills (saga) into short stories for class X students of SMA N 1 Gunung because tcount > ttable (6.96 > 1.68).